Case Report: A rare case of Epstein–Barr virus mucocutaneous ulcers occurring in the eyeball and literature review - Ke, Xiaokang; Zhang, Qingping; Huang, Wenxian; Rao, Jie; Ren, Jiacai; Wu, Juan; Yan, Honglin; Yuan, Jing; Yuan, Jingping; He, Huihua (Frontiers in Medicine, 2026)
BackgroundEpstein–Barr virus (EBV)-positive mucocutaneous ulcer (EBVMCU) is a shallow, sharply circumscribed, unifocal mucosal or cutaneous ulcer that often occurs in patients with immunosuppression.Case presentationWe report the case of a 79-year-old woman who underwent left eye keratoplasty for a corneal ulcer and continued topical immunosuppressive therapy after the operation, resulting in left eyeball lesions. Microscopically, the lesion is primarily located in the cornea and extends to the surrounding iris and choroidal tissues. Squamous epithelial ulceration and necrosis with exfoliation on the corneal surface and atypical lymphocytes of various sizes were observed, accompanied by dense polymorphic infiltration of various inflammatory cells, such as small lymphocytes, histiocytes, plasma cells, and eosinophils. These atypical cells had abundant cytoplasm with vesicular chromatin, distinct nucleoli, and scattered large cells resembling Hodgkin and Reed-Sternberg (HRS)-like cells. Immunohistochemistry and in situ hybridization (ISH) assays revealed that the atypical lymphocytes were positive for CD20, PAX5, CD30, MUM1, OCT-2, and EBV-encoded mRNA (EBER). Based on these findings, a diagnosis of EBVMCU of the left eyeball was rendered.ConclusionTo our knowledge, there are no reports of EBVMCU presenting as ocular lesions in the published literature. Therefore, understanding its specificity is very important for the correct diagnosis of this disease and to prevent misdiagnosis and mistreatment.